2024
DOI: 10.1101/2024.04.02.24305212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatially and Temporally Precise Microbiome Profiling in the Small Intestine using the SIMBA Capsule with X-ray tracking

Gang Wang,
Sharanya Menon,
Lynn Wilsack
et al.

Abstract: Few minimally invasive options for sampling the small intestinal (SI) luminal fluid exist to study the SI microbiota in health and disease. To address the lack of tools and methods to study GI regions that are difficult to access, Nimble Science developed a fully autonomous and passive sampling method, the Small Intestine MicroBiome Aspiration (SIMBATM) capsule, for convenient, high-quality, and reliable sampling to study the diet-microbiota interactions in the SI. The sealing efficacy and microbial DNA preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Indeed, SIMBA capsules were effective in collecting SI samples with variability on par with endoscopy, and high reproducibility across study visits (at least 1 week apart) with no significant differences observed in both 16S and metabolomics profiling compared to feces. Compared to a previous study [7], we did note an unexpected increase in SIMBA capsule samples with low total sequencing depth (< 1000 reads), reflected by a decrease in 16S profile microbiome diversity, which was attributed to suboptimal 16S primer selection. For example, previously using a V3-V4 primer for 16S amplicon sequencing resulted in a sequencing depth of 7 x 10 4 for SIMBA capsule samples, which was roughly equivalent to the sequencing depth obtained from corresponding fecal samples, despite an over 100 average fold difference in DNA concentration.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Indeed, SIMBA capsules were effective in collecting SI samples with variability on par with endoscopy, and high reproducibility across study visits (at least 1 week apart) with no significant differences observed in both 16S and metabolomics profiling compared to feces. Compared to a previous study [7], we did note an unexpected increase in SIMBA capsule samples with low total sequencing depth (< 1000 reads), reflected by a decrease in 16S profile microbiome diversity, which was attributed to suboptimal 16S primer selection. For example, previously using a V3-V4 primer for 16S amplicon sequencing resulted in a sequencing depth of 7 x 10 4 for SIMBA capsule samples, which was roughly equivalent to the sequencing depth obtained from corresponding fecal samples, despite an over 100 average fold difference in DNA concentration.…”
Section: Discussioncontrasting
confidence: 93%
“…Further investigation determined that the most likely cause was the choice of a suboptimal primer for PCR amplification, as a previous study using a primer spanning the V3-V4 region generated an overall 10-fold increase in read depth (i.e. a minimum depth of 3 x 10 4 total reads across 80 capsule samples) [7]. No significant difference in microbiome composition was observed between capsules which finished sampling in the jejunum vs. Ileum vs. colon (PERMANOVA p-value ~ 0.344, R 2 ~ 0.1) nor by participant IBS status (PERMANOVA p-value ~ 0.2, R 2 ~ 0.13), and did not substantially change with the inclusion of samples with lower sequencing depth.…”
Section: X-ray Tracking Profiling Demonstrates That the Simba Capsule...mentioning
confidence: 99%
See 3 more Smart Citations